Porous transport layer for electrolyzed water and method for manufacturing same

By using a porous transport layer containing titanium elements in water electrolysis, the diameter of oxygen bubbles is adjusted, and the problem of difficulty in discharge of oxygen bubbles is solved, and the performance and stability of the water electrolytic cell is improved.

CN119506919APending Publication Date: 2025-02-25HYUNDAI MOTOR CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410307870.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-24
Filing Date
2024-03-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the diameter of oxygen bubbles during water electrolysis is large and it is difficult to effectively discharge to the diaphragm, resulting in a problem of reduced performance or increased pressure.

Method used

The porous transport layer composed of the first and second particles containing the titanium element is adopted. By adjusting the average diameter and surface treatment of the first and second particles, the oxygen bubbles are ensured to be small in diameter and easily discharged to the separator.

Benefits of technology

The effective discharge of oxygen bubbles is achieved, which prevents performance reduction or pressure increase due to the reduction of water introduction, and improves the performance and stability of the water electrolytic cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506919A_ABST
    Figure CN119506919A_ABST
Patent Text Reader

Abstract

The invention relates to a porous transport layer for electrolyzed water and a manufacturing method thereof. The invention specifically provides a porous transmission layer for electrolyzed water. The porous transmission layer comprises a first layer containing first particles of a titanium group element and a second layer containing second particles of the titanium group element. An average diameter of the first particles is larger than an average diameter of the second particles, and a surface of the first layer adjacent to the second layer is planarized. A method for manufacturing the same is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of Korean Patent Application No. 10-2023-0111403 filed in the Korean Intellectual Property Office on August 24, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to a porous transport layer for water electrolysis and a method for manufacturing the same, wherein the diameter of generated oxygen bubbles is small and thus the bubbles can be easily discharged to a diaphragm and problems such as performance degradation or pressure increase due to reduced introduction of reactants can be prevented. Background Art

[0004] The polymer electrolyte membrane (PEM) water electrolysis system uses electricity to convert water (H 2 O) decomposes into hydrogen (H 2 ) and oxygen (O 2 ) electrochemical conversion device. The PEM water electrolysis system operates at a high current density, produces high-purity hydrogen and oxygen due to low gas permeation through the solid electrolyte membrane, and has high stability. The PEM water electrolysis system generally includes a PEM water electrolysis stack (stack, stack, stack) and peripheral equipment for driving the PEM water electrolysis stack, and the PEM water electrolysis stack includes a plurality of PEM water electrolysis cells (chambers, cells).

[0005] The PEM water electrolyzer generally includes: a membrane-electrode assembly MEA including an electrolyte membrane, an anode electrode and a cathode electrode, and a gas diffusion layer GDL for the cathode, a porous transport layer PTL for the anode, a separator for the cathode, and a separator for the anode. Then, water introduced through the diaphragm channel for the anode is supplied to the anode via the PTL, and hydrogen produced by the cathode is discharged via the GDL and the diaphragm channel for the cathode. In the electrochemical reaction of the PEM water electrolyzer, the water supplied to the anode is decomposed into hydrogen ions (H+) and electrons and oxygen via the oxygen evolution reaction (OER), and then flows to the cathode through the electrolyte membrane and the external circuit, and hydrogen is produced via the hydrogen evolution reaction.

[0006] The PTL plays a role in uniformly distributing and / or diffusing water as a reactant on the anode surface, and discharges oxygen generated in the anode to the outside through the diaphragm, and collects and / or transfers electrons generated via electrochemical reactions. In order to maximize the function of the PTL, various physical properties such as corrosion resistance, electrical conductivity, distribution and diffusion, low surface roughness, and mechanical strength are required.

[0007] [Prior art literature]

[0008] [Patent Document]

[0009] (Patent Document 1) Korean Patent No. 1939666 (Publication Date: March 8, 2018)

[0010] (Patent Document 2) Japanese Patent Publication No. 2022-151916 (Publication Date: October 12, 2022) Summary of the invention

[0011] The present disclosure has been made to solve the above-mentioned problems occurring in the prior art while keeping the advantages achieved by the prior art intact.

[0012] Exemplary embodiments of the present disclosure provide a porous transport layer for water electrolysis and a method for manufacturing the same, wherein the diameter of generated oxygen bubbles is small and thus the bubbles can be easily discharged to a diaphragm, and problems such as performance degradation or pressure increase due to reduced introduction of water as a reactant can be prevented.

[0013] The technical problems to be solved by the present disclosure are not limited to the above-mentioned problems, and any other technical problems not mentioned herein will be clearly understood by those skilled in the art to which the present disclosure belongs from the following description.

[0014] According to an exemplary embodiment, a porous transport layer for water electrolysis includes a first layer containing first particles of a titanium group element and a second layer containing second particles of a titanium group element, wherein an average diameter of the first particles is greater than an average diameter of the second particles, and a surface of the first layer adjacent to the second layer is planarized.

[0015] The planarized surface of the first layer may have a surface roughness (Sa) of about 1.0 μm to about 10.0 μm.

[0016] The titanium group element may include at least one selected from the group consisting of titanium (Ti), zirconium (Zr), and hafnium (Hf).

[0017] The first particles may have an average diameter of about 10 μm to about 80 μm.

[0018] The second particles may have an average diameter of about 5 μm to about 70 μm.

[0019] An average diameter of the second particles may be about 3 μm to about 60 μm smaller than an average diameter of the first particles.

[0020] The first layer may have an average thickness of about 10 μm to about 500 μm, or the second layer may have an average thickness of about 10 μm to about 500 μm.

[0021] Each of the first layer and the second layer may further include one or more selected from the group consisting of nickel group elements, stainless steel (SUS), titanium (Ti), iron (Fe), and alloys thereof.

[0022] According to an exemplary embodiment, a water electrolysis cell including a porous transport layer for water electrolysis is provided. A separator for an anode may be laminated on a first layer of the porous transport layer for water electrolysis. A membrane-electrode assembly (MEA) may be laminated on a second layer of the porous transport layer for water electrolysis.

[0023] According to an exemplary embodiment, a method for manufacturing a porous transport layer for water electrolysis includes: an operation of forming a first layer and a second layer from a first layer-forming slurry containing first particles of a titanium group element and a second layer-forming slurry containing second particles of a titanium group element, respectively; a surface treatment operation of planarizing at least one surface of the first layer, and an operation of laminating the second layer on a surface of the first layer that has been surface-treated, wherein an average diameter of the first particles is greater than an average diameter of the second particles.

[0024] Through surface treatment, the surface roughness (Sa) of one surface of the first layer can be set to about 1.0 to about 10.0 μm; the average diameter of the first particles can be about 10 μm to about 80 μm; the average diameter of the second particles can be about 5 μm to about 70 μm; or the average diameter of the second particles can be about 3 μm to about 60 μm smaller than the average diameter of the first particles.

[0025] The surface treatment may include one or more methods selected from the group consisting of a cold isostatic pressing (CIP) method, a warm isostatic pressing (WIP) method, a rolling method, and a grinding method.

[0026] Each of the first layer and the second layer may be formed by at least one application method selected from the group consisting of dip coating, blade coating, comma coating, screen printing coating, slot die coating, gravure coating, lip coating, cap coating, rod coating and tape casting, respectively.

[0027] Each of the first layer forming slurry and the second layer forming slurry may further contain a solvent, a dispersant, and a binder, respectively.

[0028] The first layer forming slurry may include about 60 to about 98 parts by weight of first particles, about 10 to about 30 parts by weight of a solvent, about 0.1 to about 3 parts by weight of a dispersant, and about 0.1 to about 4 parts by weight of a binder.

[0029] The second layer forming slurry may include about 60 to about 98 parts by weight of second particles, about 10 to about 30 parts by weight of a solvent, about 0.1 to about 3 parts by weight of a dispersant, and about 0.1 to about 4 parts by weight of a binder.

[0030] The operations of forming the first layer and the second layer and laminating the second layer may be performed through a roll-to-roll scheme.

[0031] The steps of forming the first layer and the second layer may include: forming a first green sheet and a second green sheet by an application process using a first layer forming slurry containing first particles of a titanium group element and a second layer forming slurry containing second particles of a titanium group element, respectively; and degreasing the first green sheet and the second green sheet, respectively.

[0032] As discussed, the method and system suitably include the use of a controller or processor. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and other objects, features and advantages of the present disclosure will become more apparent from the following detailed description in conjunction with the accompanying drawings:

[0034] Figure 1 is a cross-sectional view of a typical polymer electrolyte membrane (PEM) water electrolysis cell;

[0035] Figure 2 is a cross-sectional view schematically showing a problem that occurs when surface treatment for planarization is not performed;

[0036] Figure 3 is a cross-sectional view of a porous transport layer according to an exemplary embodiment of the present disclosure; and

[0037] Figure 4 is a cross-sectional view of a water electrolysis cell according to an exemplary embodiment of the present disclosure. DETAILED DESCRIPTION

[0038] In the specification, when it is described that a part “includes” a certain component, this means that it can further include other components, rather than excluding other components, unless specifically stated otherwise.

[0039] The terms used herein are only used for the purpose of describing specific embodiments, and are not intended to limit the present disclosure. As used herein, unless the context clearly indicates otherwise, the singular forms "a", "one" and "the" are intended to also include plural forms. These terms are only intended to distinguish one component from another component, and these terms do not limit the nature, order or order of the components. It should also be understood that when the terms "include" and / or "include" are used in this specification, it specifies the existence of the features, integers, steps, operations, elements and / or parts, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, parts and / or their combinations. As used in this article, the term "and / or" includes any and all combinations of one or more related listed items. Throughout the specification, unless explicitly described to the contrary, the word "include" and variants such as "include" or "contain" will be understood to indicate that the elements are included, but any other elements are not excluded. In addition, the terms "unit", "device", "machine" and "module" described in the specification are meant to be used to process at least one function and operation unit, and can be implemented by hardware components or software components and combinations thereof.

[0040] Although the exemplary embodiments are described as using multiple units to perform the exemplary methods, it should be understood that the exemplary methods can also be performed by one or more modules. In addition, it should be understood that the term controller / control unit refers to a hardware device that includes a memory and a processor and is specifically programmed to perform the methods described herein. The memory is configured to store the modules, and the processor is specifically configured to perform the modules to perform one or more methods described further below.

[0041] In addition, the control logic of the present disclosure may be embodied as a non-volatile computer readable medium on a computer readable medium containing executable program instructions executed by a processor, a controller, etc. Examples of computer readable media include, but are not limited to, ROM, RAM, (CD)-ROM, magnetic tapes, floppy disks, flash drives, smart cards, and optical data storage devices. The computer readable medium may also be distributed in a network coupled computer system so that the computer readable medium is stored and executed in a distributed manner, for example, by a telematics server or a controller area network (CAN).

[0042] Unless otherwise specified or clear from the context, the term "about" as used herein should be understood to be within the normal tolerance range in the art, such as within 2 standard deviations of the mean. "About" can be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the value. Unless the context clearly indicates otherwise, all numerical values ​​provided herein are modified by the term "about".

[0043] In this specification, when it is described that a member is located on "a surface", "a surface", "an opposite surface" or "opposite surfaces" of another member, this not only means that one member contacts another member but also means that another member exists between the two members.

[0044] refer to Figure 1 , a PEM water electrolyzer generally includes a membrane-electrode assembly MEA (including an electrolyte membrane 10, an anode electrode 20, and a cathode electrode 30), a gas diffusion layer GDL 40 for the cathode, a porous transport layer PTL 50 for the anode, a separator 60 for the cathode, and a separator 70 for the anode. Then, water introduced through the separator channel "a" for the anode is supplied to the anode 20 through the PTL 50, and hydrogen generated by the cathode 30 is discharged through the GDL 40 and the separator channel "b" for the cathode. In the electrochemical reaction of the PEM water electrolyzer, water supplied to the anode is separated into hydrogen ions (H+) and electrons and oxygen via an oxygen evolution reaction (OER), and then flows to the cathode through the electrolyte membrane and an external circuit, and hydrogen is generated via a hydrogen evolution reaction.

[0045] The PTL plays the role of uniformly distributing and / or diffusing water as a reactant on the surface of the anode electrode, discharging oxygen generated in the anode electrode to the outside through the diaphragm, and collecting and / or transferring electrons generated by the electrochemical reaction. In order to maximize the function of the PTL, it must have various characteristics such as corrosion resistance, conductivity, distribution and diffusion, low surface roughness, and mechanical strength.

[0046] Therefore, for PTL, materials having excellent electrical conductivity, thermal conductivity, and corrosion resistance as well as low ohmic resistance and mass transfer loss are preferred. Therefore, conventional PTL generally contains titanium (Ti) having excellent physical and chemical properties because it does not corrode even under high potential and acidic conditions. However, due to the partial pressure difference of water flowing into PTL caused by the shape of the anode diaphragm channel "a", water cannot be uniformly supplied to the anode.

[0047] As an alternative measure to this problem, various methods for controlling the horizontal pore shape of the contact surface between the PTL and the anode have been proposed. For example, Korean Patent No. 1939666 (Patent Document 1) discloses a method for manufacturing a corrosion-resistant gas diffusion layer using titanium fibers and a gas diffusion layer manufactured thereby. However, in a GDL or PTL manufactured by using titanium fibers as in Patent Document 1, in a kW-class water electrolysis cell operating at high temperature and high pressure, the fibers break and pinholes are generated in the electrolyte membrane, which can cause crossover of the cathode and / or anode, and durability can be deteriorated due to short circuits in the system.

[0048] In addition, Japanese Patent Publication No. 2022-151916 (Patent Document 2) discloses a titanium porous plate including a sintered body of titanium or a titanium alloy, and the titanium porous plate has a structure in which a first layer and a second layer are laminated in a thickness direction thereof, and an average pore size of the second layer is larger than an average pore size of the first layer. However, when the first layer is manufactured using a first slurry as in Patent Document 2 and then the second layer is manufactured on the first layer by using a second slurry, it is difficult to manufacture the second layer having a uniform thickness due to the titanium powder included in the first layer (see Figure 2 (a)). In addition, even when individual layers are manufactured rather than manufacturing a slurry and then laminating, void spaces may be caused due to the greater surface roughness of the first layer, whereby oxygen is trapped (see Figure 2 (b)).

[0049] Specifically, Figure 2 As shown in (a), when the surface roughness of the first layer is large, some areas (its protrusions) are not coated, or some areas (its depressions) have holes, because the slurry is concentrated in the direction of gravity, so that clogging can occur. In addition, in the case of no coating, the advantages of the multilayer structure are lost, and in the dense area of ​​over-coating, the holes can become blocked and quality deviations can occur, such as the multiphase fluid diffusion can become uneven.

[0050] In addition, if Figure 2 As shown in (b), when a lamination process is used, the second layer can be formed to have a uniform thickness, but a void space is generated between the first layer and the second layer, thereby trapping oxygen and increasing the capillary pressure, and thus the oxygen may not be properly removed, resulting in hindering the inflow of reactants, so that its performance may be reduced or the pressure may be increased.

[0051] Furthermore, second particles with a smaller diameter may enter between pores of the first layer and thus a third layer including the first particles and the second particles may be formed, whereby mass transfer resistance and differential pressure increase, and quality deviation may occur.

[0052] Therefore, by adjusting the diameter of the generated oxygen bubbles, they can be easily discharged to the diaphragm, and water as a reactant can be introduced, so that a porous transport layer of a water electrolysis cell including the same having excellent performance can be manufactured, and therefore, research and development of a method for manufacturing the porous transport layer having excellent processability, low performance deviation and position-related quality deviation of manufactured products, and excellent economic performance due to application in a roll-to-roll scheme has been required.

[0053] Porous transport layer for water electrolysis

[0054] The porous transport layer for water electrolysis according to the present disclosure includes a first layer containing first particles of a titanium group element and a second layer containing second particles of a titanium group element, wherein the average diameter of the first particles is greater than the average diameter of the second particles, and the surface of the first layer adjacent to the second layer may be flattened. Then, the first layer may have a higher porosity than the second layer, or the average pore size of the first layer may be greater than the average pore size of the second layer.

[0055] As described above, the porous transport layer in the present invention includes a first layer and a second layer containing particles having different average diameters, wherein the diameter of the generated oxygen bubbles can be adjusted so that the oxygen bubbles are easily discharged to the diaphragm, the performance of the water electrolysis cell including it can be further enhanced by promoting the inflow of water as a reactant, and the membrane electrode assembly MEA as an adjacent component can be protected. In addition, the surface of the first layer adjacent to the second layer is flattened, so that the second layer can be easily manufactured to have a uniform thickness, and thus the workability can become excellent, the thickness deviation of the manufactured product can be reduced, and the performance variation and the position-related quality variation can be reduced.

[0056] refer to Figure 3 , the porous transport layer 50 for water electrolysis according to the present disclosure may include a first layer 110 including first particles 100 and a second layer 210 including second particles 200 .

[0057] First floor

[0058] The function of the first layer is to distribute and diffuse water introduced as a reactant into the PTL, and to smoothly discharge oxygen generated by the anode to the outside through the separator.

[0059] The surface of the first layer adjacent to the second layer is flattened. Therefore, the roughness of the surface of the first layer on the side contacting the second layer can be adjusted, and thus the second layer can be easily manufactured to have a uniform thickness, thereby ensuring excellent processability, and reducing thickness deviation, performance deviation, and position-related quality deviation.

[0060] In addition, the planarized surface of the first layer may have a surface roughness (Sa) of 1.0 μm to 10.0 μm or 1.5 μm to 5.0 μm. When the surface roughness of the planarized first layer is less than the above range, the roughness is too low and the manufacturing difficulty is very high, so that the first layer cannot be manufactured, the process performance may be reduced, or the process cost may increase. At the same time, when it is greater than the above range, the second layer is formed to have an uneven thickness, and the thickness deviation of the final product as PTL is too large, so that the proper bonding between PTL and MEA cannot be achieved on the surface contacting MEA, and therefore the surface pressure is uneven or the generated oxygen can be trapped in the non-bonding area and the introduction of water as a reactant is prevented, and therefore the performance may be degraded.

[0061] The first layer may include first particles of a titanium group element.

[0062] In addition, the titanium group element of the first layer may include, for example, at least one selected from the group consisting of titanium (Ti), zirconium (Zr) and hafnium (Hf). Specifically, the titanium group element of the first layer may include titanium. Then, the first layer may further include nickel (Ni) and / or stainless steel (SUS) to save raw materials.

[0063] As long as the first particles have a shape that can be used when manufacturing PTL, for example, they may be circular, oval, or irregular, they may be generally used without particular limitation.

[0064] In addition, the first particles may have an average diameter of 10 μm to 80 μm, 10 μm to 60 μm, or 10 μm to 50 μm. When the average diameter of the first particles is less than the above range, the porosity of the manufactured first layer is too low or the pore size is too small, whereby the introduction of water and the discharge of oxygen are not smooth, and therefore, high mass transfer resistance is caused and performance is reduced in the high current section. At the same time, when it is greater than the above range, the porosity of the manufactured first layer is too large, whereby the process performance when forming the second layer is deteriorated, and the fluid diffusion rate is low, and thus the performance is reduced. Then, the average diameter of the first particles may be a diameter (D50) at which the cumulative distribution is 50% in the diameter distribution measured by using a particle size analyzer PSA.

[0065] The average diameter of the second particles is smaller than the average diameter of the first particles. For example, the average diameter of the second particles may be 3 μm to 60 μm, 5 μm to 50 μm, or 5 μm to 40 μm smaller than the average diameter of the first particles. When the difference between the average diameter of the first particles and the average diameter of the second particles is less than the above range, the advantages of the double layer (first layer and second layer) for protecting the membrane electrode assembly, increasing mass transfer, and controlling the size of oxygen bubbles may be reduced, and when the above range is exceeded, appearance defects such as bending may occur due to different thermal shrinkage rates of the layers during heat treatment and sintering (i.e., due to differences in thermal shrinkage rates).

[0066] The first layer may have an average thickness of 10 μm to 500 μm, 30 μm to 400 μm, or 30 μm to 300 μm. When the average thickness of the first layer is less than the above range, the hardness of the manufactured product may be low, thereby deteriorating the operating performance or easily breaking, or the process performance may be deteriorated when the second layer is formed, and when it is greater than the above range, the thickness of the final product may become too large, and thus the mass transfer resistance may be increased.

[0067] In addition, the first layer may have an average pore size of 3 μm to 40 μm, 5 μm to 30 μm, or 8 μm to 25 μm. When the average pore size of the first layer is less than the above range, the pore size of the first layer is so small that the introduction of water and the discharge of oxygen are limited, and when it is greater than the above range, the surface roughness of the first layer is high, thereby making it difficult to form the second layer, or the second layer forming slurry may penetrate into the pores of the first layer, or the thickness of the final product has a large deviation when the second layer is formed. Then, the average pore size of the first layer may be a pore size measured by mercury immersion pore size analysis.

[0068] Second floor

[0069] The second layer may directly contact the membrane electrode assembly MEA, play a role in uniformly distributing water introduced as a reactant from the first layer into the membrane electrode assembly, and adjust the generated oxygen to a suitable diameter to easily discharge oxygen while a direct OER reaction occurs.

[0070] The second layer includes second particles of a titanium group element.

[0071] In addition, the titanium group element of the second layer may include, for example, at least one selected from the group consisting of titanium (Ti), zirconium (Zr) and hafnium (Hf). Specifically, the titanium group element in the second layer may include titanium. Then, the second layer may further include nickel (Ni) and / or stainless steel (SUS) to save raw materials.

[0072] As long as the second particles have a shape that can be used to produce a PTL, for example, they may be circular, oval, or irregular, they may be generally used without particular limitation.

[0073] In addition, the second particles may have an average diameter of 5 μm to 70 μm, 6 μm to 60 μm, or 7 μm to 45 μm. When the average diameter of the second particles is less than the above range, the pore size of the second layer is too small or the porosity is too low, thereby excessively reducing the path for introducing water and discharging the generated oxygen bubbles, and thus the performance may be reduced, and when it is greater than the above range, the roughness on the surface in contact with the MEA may be too high, and thus problems such as damaging the MEA or increasing the contact resistance may be caused. Then, the average diameter of the second particles may be a diameter (D50) at which the cumulative distribution is 50% in the diameter distribution measured by using a particle size analyzer PSA.

[0074] The second layer may have an average thickness of 10 μm to 500 μm, 20 μm to 400 μm, or 30 μm to 300 μm. When the average thickness of the second layer is less than the above range, the performance may be reduced because a space for properly diffusing the reaction fluid and the generated fluid cannot be provided, and when it is greater than the above range, the thickness of the PTL as a final product is too high, and the mass transfer resistance may become too high in the high current section, and the performance of the porous transport layer may be reduced.

[0075] In addition, the second layer may have an average pore size of 3 μm to 30 μm, 4 μm to 20 μm, or 5 μm to 10 μm. When the average pore size of the second layer is less than the above range, the porosity of the second layer is too low or the pore size is too small, thereby limiting the introduction of water and the removal of oxygen bubbles, and when it is greater than the above range, the surface roughness may increase, damaging the MEA, or the size of the oxygen bubbles may increase, thereby limiting the introduction of water. Then, the average pore size of the second layer may be a pore size measured by mercury immersion pore size analysis.

[0076] Each of the first layer and the second layer may further include one or more selected from the group consisting of nickel group elements, stainless steel (SUS), titanium (Ti), iron (Fe), and alloys thereof, respectively.

[0077] The porous transport layer for water electrolysis according to the present disclosure can make the generated oxygen bubbles have a smaller diameter, so that they are easily discharged into the diaphragm, and water as a reactant can be easily introduced, so that the performance of the water electrolysis cell containing it is excellent. In addition, according to the porous transport layer for water electrolysis, each layer with a uniform thickness can be easily manufactured, so that the performance variation and site-specific quality variation in the water electrolysis cell containing it are low.

[0078] Water electrolysis cell

[0079] The water electrolysis cells of the present disclosure may include a porous transport layer as described above.

[0080] For example, the separator for the anode may be laminated on the first layer of the porous transport layer for water electrolysis. In addition, the membrane-electrode assembly MEA may be laminated on the second layer of the porous transport layer for water electrolysis.

[0081] Specifically, refer to Figure 4 , the water electrolysis cell "A" according to the present disclosure may include the following form, wherein a separator 70 for an anode, a porous transport layer PTL 50 including a first layer 110 and a second layer 210, a membrane-electrode assembly (MEA) 200 including an anode electrode 20, an electrolyte membrane 10 and a cathode electrode 30, a gas diffusion layer GDL 40, and a separator 60 for a cathode are sequentially laminated.

[0082] Method for making porous transport layer for water electrolysis

[0083] The method for manufacturing a porous transport layer for water electrolysis according to the present disclosure may include: an operation of forming a first layer and a second layer from a first layer-forming slurry containing first particles of a titanium group element and a second layer-forming slurry containing second particles of a titanium group element, respectively; a surface treatment operation of flattening at least one surface of the first layer; and an operation of laminating the second layer on a surface of the first layer on which the surface treatment has been performed.

[0084] Operations of forming the first and second layers

[0085] In this operation, the first layer and the second layer are formed from a first layer forming slurry containing first particles of a titanium group element and a second layer forming slurry containing second particles of a titanium group element, respectively.

[0086] The average diameter of the first particles is greater than the average diameter of the second particles. Then, the shape and average diameter of each of the first particles and the second particles of the titanium group element are the same as those described in the porous transport layer.

[0087] Each of the first layer forming slurry and the second layer forming slurry may further include a solvent, a dispersant, and a binder, respectively.

[0088] <First layer forming slurry>

[0089] The solvent is used to improve workability by adjusting the viscosity of the slurry. Then, as long as the solvent is a solvent that can be used for PTL production, and may include ethanol or toluene, for example, it may be generally used without particular limitation.

[0090] In addition, the solvent may be included in an amount of 10 to 30 parts by weight, 15 to 30 parts by weight, or 20 to 30 parts by weight relative to 100 parts by weight of the first layer forming slurry. When the solvent content in the first layer forming slurry is less than the above range, the viscosity of the first layer forming slurry is high and the coating characteristics are deteriorated, whereby the thickness of the first layer is unevenly formed or the position-dependent porosity and / or pore size deviation of the first layer may become too large, and when it is greater than the above range, during the sintering process, due to excessive evaporation of the solvent, materials and equipment may be contaminated, or it may be difficult to match the target thickness, porosity, and / or pore size.

[0091] The dispersant can improve the dispersion of the first particles in the slurry and help form a coating film of uniform composition. Then, as long as the dispersant is used when manufacturing the PTL, for example, it can include one or more selected from the group consisting of: water, ethanol, methanol, isopropanol, xylene, cyclohexanone, acetone, toluene and methyl ethyl ketone, it can be generally used without particular limitation.

[0092] In addition, the dispersant may be included in an amount of 0.1 to 3 parts by weight, 1 to 3 parts by weight, or 1.5 to 2.3 parts by weight relative to 100 parts by weight of the first layer forming slurry. When the content of the dispersant in the first layer forming slurry is less than the above range, the first particles may agglomerate with each other when the slurry is manufactured, and when it is greater than the above range, the viscosity of the slurry is too low, thereby insufficient processability of the coating process.

[0093] The binder can improve the adhesion between the first particles in the slurry and help to easily form it into a sheet. Then, as long as the binder is used when manufacturing PTL, for example, it can include one or more selected from the group consisting of polyvinyl butyral (PVB), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), polyvinyl acetate (PVAc) and polyacrylonitrile, it can be generally used without particular limitation.

[0094] In addition, the binder may be included in an amount of 0.1 to 4 parts by weight, 1 to 4 parts by weight, or 2 to 3.5 parts by weight relative to 100 parts by weight of the first layer forming slurry. When the content of the binder in the first layer forming slurry is less than the above range, the adhesive force between the first particles in the manufactured first layer is insufficient and it is difficult to maintain the sheet shape, and when it is greater than the above range, the adhesive force of the components in the slurry is too strong, thereby it adheres to the lower substrate.

[0095] Specifically, the first layer forming slurry may include 60 to 98 parts by weight of the first particles, 10 to 30 parts by weight of the solvent, 0.1 to 3 parts by weight of the dispersant, and 0.1 to 4 parts by weight of the binder, relative to 100 parts by weight of the slurry. More specifically, the first layer forming slurry may include 65 to 90 parts by weight or 70 to 85 parts by weight of the first particles, 15 to 30 parts by weight or 20 to 30 parts by weight of the solvent, and 1 to 3 parts by weight or 1.5 to 2.3 parts by weight of the dispersant, and 1 to 4 parts by weight or 2 to 3.5 parts by weight of the binder.

[0096] When the content of the first particles in the first layer forming slurry is less than the above range, the distance between the first particles may be longer during the heat treatment process, so that sintering cannot occur smoothly, or the porosity of the manufactured first layer may be too high or the hardness may be too low, and when it exceeds the above range, the porosity of the manufactured first layer may be too low or the viscosity of the slurry may be too high, so that the first raw sheet cannot be manufactured normally.

[0097] In addition, the first layer forming slurry can be manufactured by specifically mixing and stirring the first particles, solvent, dispersant and binder through a ball milling process. Then, the stirring time period can be 1 hour or longer, 10 to 30 hours, 12 to 24 hours or 18 to 24 hours, but the present disclosure is not limited thereto and can be any time period that allows uniform mixing.

[0098] The first layer forming slurry may have a viscosity of 1,000 to 8,000 cP, 1,500 to 7,500 cP, or 1,800 to 7,000 cP at 25° C. When the viscosity of the first layer forming slurry at 25° C. is within the above range, the slurry application processability is excellent and the thickness of the manufactured first layer can be uniformly formed. In addition, when the viscosity of the first layer forming slurry at 25° C. is less than the above range, the surface roughness of the first layer increases due to the uneven thickness of the manufactured first layer, and when it is greater than the above range, the slurry application processability may be insufficient.

[0099] <Second layer forming slurry>

[0100] The solvent, dispersant and binder in the second layer forming slurry are as described in the solvent, dispersant and binder in the first layer forming slurry, and the solvent, dispersant and binder in the slurry may be the same as or different from each other.

[0101] In addition, the solvent may be included in an amount of 10 to 30 parts by weight, 15 to 30 parts by weight, or 20 to 30 parts by weight relative to 100 parts by weight of the second layer forming slurry. When the solvent content in the slurry for forming the second layer is less than the above range, the viscosity of the second layer forming slurry is high and the coating performance is reduced, the thickness of the second layer is formed unevenly, or the deviation of the position-dependent porosity and / or pore size of the second layer may be too large, and when it is greater than the above range, the material and the equipment may be contaminated due to excessive evaporation of the solvent during sintering, or it may be difficult to match the target thickness, porosity, and / or pore size.

[0102] The dispersant may be included in an amount of 0.1 to 3 parts by weight, 1 to 3 parts by weight, or 1.5 to 2.3 parts by weight relative to 100 parts by weight of the second layer forming slurry. When the content of the dispersant in the second layer forming slurry is less than the above range, the second particles agglomerate with each other when the slurry is manufactured, and when it is greater than the above range, the viscosity of the slurry is too low and the workability for the coating process is insufficient.

[0103] In addition, the binder may be included in an amount of 0.1 to 4 parts by weight, 1 to 4 parts by weight, or 2 to 3.5 parts by weight relative to 100 parts by weight of the second layer forming slurry. When the content of the binder in the second layer forming slurry is less than the above range, it is difficult to maintain the sheet shape due to insufficient adhesion between the second particles in the manufactured second layer, and when it is greater than the above range, the adhesion of the components in the slurry may be too strong and may adhere to the lower substrate during application.

[0104] Specifically, the second layer forming slurry may include 60 to 98 parts by weight of the second particles, 10 to 30 parts by weight of the solvent, 0.1 to 3 parts by weight of the dispersant, and 0.1 to 4 parts by weight of the binder, relative to 100 parts by weight of the slurry. More specifically, the second layer forming slurry may include 65 to 90 parts by weight or 70 to 85 parts by weight of the second particles, 15 to 30 parts by weight or 20 to 30 parts by weight of the solvent, and 1 to 3 parts by weight or 1.5 to 2.3 parts by weight of the dispersant, and 1 to 4 parts by weight or 2 to 3.5 parts by weight of the binder.

[0105] When the content of the second particles in the second layer forming slurry is less than the above range, the distance between the second particles is longer during the heat treatment process, so that sintering may not proceed smoothly, or the porosity of the manufactured second layer may be too high or the hardness may be too low, and when it is greater than the above range, the porosity of the manufactured second layer is too low or the viscosity of the slurry is too high, making it impossible to normally manufacture the second raw sheet.

[0106] In addition, the second layer forming slurry can be manufactured by a ball milling process by specifically mixing and stirring the second particles, solvent, dispersant and binder. Then, the stirring time can be 1 hour or longer, 10 to 30 hours, 12 to 24 hours or 18 to 24 hours, but the present disclosure is not limited thereto and can be any time period that allows uniform mixing.

[0107] The second layer forming slurry may have a viscosity of 1,000 to 8,000 cP, 1,500 to 7,500 cP, or 1,800 to 7,000 cP at 25° C. When the viscosity of the second layer forming slurry at 25° C. is within the above range, the slurry application processability is excellent and the thickness of the manufactured second layer can be uniformly formed. In addition, when the viscosity of the second layer forming slurry at 25° C. is less than the above range, the surface roughness of the second layer increases due to the uneven thickness of the manufactured second layer, and when it is greater than the above range, the slurry application processability may be insufficient.

[0108] <Method for Forming First Layer and Second Layer>

[0109] Each of the first layer and the second layer may be formed by at least one application method selected from the group consisting of dip coating, blade coating, comma coating, screen printing coating, slot die coating, gravure coating, lip coating, cap coating, rod coating, and tape casting. Specifically, each of the first layer and the second layer may be formed by a blade coating method.

[0110] Specifically, the operation of forming the first layer and the second layer may include: the operation of forming the first raw sheet and the second raw sheet by an application process using a first layer forming slurry containing first particles of a titanium group element and a second layer forming slurry containing second particles of a titanium group element, respectively, and the operation of degreasing the first raw sheet and the second raw sheet, respectively.

[0111] The application process may use any of the methods described above.

[0112] For example, in the operation of forming the first layer and the second layer, the first green sheet and the second green sheet can be formed respectively using the first layer forming slurry and the second layer forming slurry by using a doctor blade method, and when manufacturing the green sheet, an application method of a tape casting method at a speed of 0.3 m / min to 1 m / min can be used. While manufacturing the green sheet, the shape can be adjusted by appropriately positioning the doctor blade and release paper so that the slurry can reach the embossed area during the application process.

[0113] When the application method as described above is performed, any commonly used and / or purchased release paper can be used without particular limitation, for example, the release paper can include any one of polyethylene terephthalate (PET), polyethylene naphthalate (PEN) and polyethylene cyclohexanedimethanol terephthalate (PCT). In addition, the embossed area (i.e., pattern layer) can be used without particular limitation, as long as it is commonly used and / or commercially available, for example, it can include any one of low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE) and thermoplastic polyurethane (TPU), unstretched polypropylene (CPP) and polyvinylidene fluoride (PVDF).

[0114] Each of the first green sheet and the second green sheet manufactured by the application process may be degreased separately. That is, each of the first green sheet and the second green sheet manufactured by the application process may be degreased separately and then laminated. By degreasing, a slip phenomenon at the interface between the layers during lamination can be prevented.

[0115] The solvent in the first green sheet and the second green sheet may be removed by degreasing treatment. For example, the degreasing treatment may be performed at 300 to 700° C., 350 to 600° C., or 400 to 500° C. in an inert gas atmosphere. When the temperature during the degreasing treatment is lower than the above range, the solvent may remain without evaporating, whereby the performance of the PTL may be deteriorated, and when it is higher than the above range, the titanium element may be oxidized in an environment other than a high vacuum atmosphere, whereby the performance of the PTL may be deteriorated.

[0116] In addition, the inert gas may be a commonly used inert gas, for example, it may be argon (Ar) gas.

[0117] The degreasing treatment may be performed by increasing the temperature at a rate of 1 to 5° C. / min or 1 to 3° C. / min and maintaining the degreasing treatment temperature for 1 to 4 hours or 1 to 3 hours.

[0118] Surface treatment operations

[0119] In this operation, surface treatment may be performed to planarize at least one surface of the first layer.

[0120] The surface treatment is to flatten at least one side of the first layer, and the surface roughness of the first layer bonded to the second layer can be adjusted, so that the second layer can be easily manufactured to a uniform thickness, and therefore, the processability becomes excellent and the performance variation and position-related quality variation of the manufactured product are small.

[0121] Additionally, surface treatment may be performed on opposite sides of the first layer to planarize the opposite sides of the first layer.

[0122] The surface treatment may include one or more methods selected from the group consisting of a cold isostatic pressing (CIP) method, a warm isostatic pressing (WIP) method, a rolling method, and a grinding method.

[0123] In addition, through surface treatment, the surface roughness (Sa) of one side of the first layer can be set to 1.0 μm to 10.0 μm or 1.5 μm to 5.0 μm. When the surface roughness of the surface-treated first layer is less than the above range, the surface roughness of the first layer is too low, thereby the manufacturing difficulty is very high, and thus the process performance is deteriorated, and when it is greater than the above range, a second layer with uneven thickness is formed, thereby the thickness deviation of the final product as PTL is large, and the surface pressure between PTL and MEA on the surface contacting MEA is unevenly formed, and therefore, the performance may be low or uneven problems may occur.

[0124] Lamination Operation

[0125] In this operation, the second layer may be laminated on one surface of the first layer which has been surface-treated.

[0126] For example, lamination can be performed by a roll-to-roll method. Specifically, the operation of forming the first layer and the second layer and the lamination operation can be performed by a roll-to-roll method. More specifically, in the operation of forming the first layer and the second layer, each of the first layer forming slurry and the second layer forming slurry is used by a roll-to-roll method to form a first raw sheet and a second raw sheet by using a doctor blade method, and the first raw sheet and the second raw sheet can be degreased, respectively, and the degreased first raw sheet and the second raw sheet can be laminated by a roll-to-roll method. As described above, when the PTL is manufactured by applying a roll-to-roll method, the manufacturing method of the present disclosure is economical because it reduces process costs compared to conventional manufacturing methods using electroplating and has excellent process efficiency.

[0127] Furthermore, a laminated body produced by laminating the second layer on one surface of the first layer on which the surface treatment has been performed can be joined to prevent a slip phenomenon at the interface of each layer.

[0128] The bonding may be performed at 100 to 150° C. or 110 to 140° C. while applying a pressure of 0.1 to 5 MPa or 0.5 to 4 MPa. When the temperature during bonding is higher than the above range, i.e., during bonding at a high temperature, the solvent and / or the adhesive in the first layer and the second layer may evaporate and cracks may be generated, and when it is lower than the above range, a higher load is required, whereby device stability is reduced or process cost is increased.

[0129] In addition, when the pressure during bonding is greater than the above range, the thickness of the layer may become thinner, the layer may be broken or mixed, and the performance of the water electrolysis cell manufactured thereby may be deteriorated, while when the pressure is less than the above range, the pore size in the manufactured PTL may deviate from the target value, and thus the performance may be deteriorated.

[0130] The manufacturing method may further include an operation of manufacturing a porous transmission layer by sintering the laminated body after the operation of laminating the layers as described above.

[0131] Sintering operation

[0132] The sintering may be performed at a temperature and pressure applicable when manufacturing the PTL, for example, at a temperature of 900 to 1,500° C., 950 to 1,400° C., or 1,000 to 1,300° C. In addition, the sintering may be performed at a temperature of 10 -5 Torr or smaller, 10 -8 Up to 10 -5 Torr or 10 -7 Up to 5×10 -6 Sintering is carried out under a vacuum degree of 100°.

[0133] When the temperature during sintering is lower than the above range, the titanium group element may not be sintered, whereby the pores in the PTL are excessively large or the rigidity becomes weak, whereas when the temperature is higher than the above range, the titanium group element may be over-sintered and the pores may be clogged.

[0134] In addition, when the vacuum degree during sintering is lower than the above range, the titanium element may be oxidized at high temperature or the PTL may be contaminated due to contaminants in the sintering furnace, and when the vacuum degree is higher than the above range, a vacuum pump of higher specifications than required may be required, and thus the process cost may increase.

[0135] The method of manufacturing a porous transport layer according to the present disclosure as described above can be easily manufactured to have a uniform thickness, and thus the performance deviation and position-related quality deviation of the manufactured product are small, and a roll-to-roll method can be applied, and the process cost and process efficiency are very excellent, and therefore it is economical.

[0136] According to the porous transport layer of the present disclosure, the generated oxygen bubbles have a small diameter, whereby the bubbles can be easily discharged into the separator, and water as a reactant can be easily introduced, and thus the performance of a water electrolytic cell including the same is excellent.

[0137] In addition, according to the manufacturing method of the porous transport layer, a layer with uniform thickness can be easily manufactured, so the workability is excellent, the performance deviation and position-related quality deviation of the manufactured product are low, and by applying a roll-to-roll scheme, it has excellent economic efficiency.

Claims

1. A porous transport layer for water electrolysis, comprising: a first layer of first particles comprising a titanium group element, and The second layer of the second particles containing a titanium group element, wherein the average diameter of the first particles is greater than the average diameter of the second particles, and The surface of the first layer adjacent to the second layer is planarized. 2 . The porous transport layer of claim 1 , wherein the planarized surface of the first layer has a surface roughness of 1.0 μm to 10.0 μm. 3 . The porous transmission layer according to claim 1 , wherein the titanium group element includes at least one selected from the group consisting of titanium (Ti), zirconium (Zr), and hafnium (Hf). The porous transport layer according to claim 1 , wherein the first particles have an average diameter of 10 μm to 80 μm. The porous transport layer according to claim 1 , wherein the average diameter of the second particles is 5 μm to 70 μm. 6 . The porous transmission layer of claim 1 , wherein an average diameter of the second particles is 3 μm to 60 μm smaller than an average diameter of the first particles. 7 . The porous transmission layer according to claim 1 , wherein the first layer has an average thickness of 10 μm to 500 μm, or the second layer has an average thickness of 10 μm to 500 μm.

8. The porous transmission layer according to claim 1, wherein each of the first layer and the second layer further comprises one or more selected from the group consisting of nickel group elements, stainless steel, titanium (Ti), iron (Fe), and alloys thereof.

9. A water electrolysis cell comprising the porous transport layer for water electrolysis according to claim 1.

10. The water electrolysis cell according to claim 9, wherein a separator for an anode is laminated on the first layer of the porous transport layer for water electrolysis.

11. The water electrolysis cell according to claim 9, wherein a membrane electrode assembly is laminated on the second layer of the porous transport layer for water electrolysis.

12. A method of making a porous transport layer for water electrolysis, the method comprising: The first layer and the second layer are formed from a first layer forming slurry containing first particles of a titanium group element and a second layer forming slurry containing second particles of a titanium group element, respectively. performing a surface treatment to planarize at least one surface of the first layer, and laminating the second layer on one surface of the first layer on which the surface treatment has been performed, The average diameter of the first particles is greater than the average diameter of the second particles.

13. The method according to claim 12, wherein through the surface treatment, the surface roughness of one surface of the first layer is set to 1.0 μm to 10.0 μm, wherein the average diameter of the first particles is 10 μm to 80 μm, wherein the average diameter of the second particles is 5 μm to 70 μm, or wherein the average diameter of the second particles is 3 μm to 60 μm smaller than the average diameter of the first particles.

14. The method according to claim 12, wherein the surface treatment comprises one or more methods selected from the group consisting of cold isostatic pressing, warm isostatic pressing, rolling and grinding.

15. The method according to claim 12, wherein each of the first layer and the second layer is formed by at least one application method selected from the group consisting of dip coating, doctor blade coating, comma coating, screen printing coating and slot die coating, gravure coating, lip coating, cap coating, rod coating and tape casting. 16 . The method according to claim 12 , wherein each of the first layer forming slurry and the second layer forming slurry further comprises a solvent, a dispersant, and a binder, respectively. 17 . The method according to claim 16 , wherein the first layer forming slurry comprises 60 to 98 parts by weight of the first particles, 10 to 30 parts by weight of the solvent, 0.1 to 3 parts by weight of the dispersant, and 0.1 to 4 parts by weight of the binder. 18 . The method according to claim 16 , wherein the second layer forming slurry comprises 60 to 98 parts by weight of the second particles, 10 to 30 parts by weight of the solvent, 0.1 to 3 parts by weight of the dispersant, and 0.1 to 4 parts by weight of the binder.

19. The method of claim 12, wherein the operations of forming the first layer and the second layer and laminating the second layer are performed by a roll-to-roll scheme.

20. The method of claim 19, wherein forming the first layer and the second layer comprises: forming a first green sheet and a second green sheet by an application process using the first layer forming slurry containing the first particles of the titanium group element and the second layer forming slurry containing the second particles of the titanium group element, respectively; and The first green sheet and the second green sheet are degreased respectively.

Citation Information

Patent Citations

  • Titanium porous plate, and electrode for water electrolysis, water electrolysis apparatus

    JP2022151916A

  • Gas diffusion layer with corrosion protective coating and method for manufacturing thereof, and membrane electrode assembly having the gas diffusion layers

    KR101939666B1

  • Tape cutter

    KR1020230111403A